The Role of Capital Structure in Mediating the Effects of Profitability and Firm Size on Firm Value - Dwi Yusrani Anugrah; Taufiqur Rohman (Muhasabatuna : Jurnal Akuntansi Syariah, 2026)
This study is designed to examine the extent to which profitability and firm size exert influence on firm value, with capital structure positioned as an intervening variable. The research was conducted on companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange (IDX) over the period of 2021 to 2023. A quantitative approach was employed, utilizing path analysis as the primary analytical technique. Sampling was carried out through purposive sampling, wherein the main criterion was companies that published annual financial reports in rupiah currency during the study period. Empirical findings reveal that profitability exerts a negative effect on capital structure, whereas firm size positively influences it. Meanwhile, profitability has been found to positively affect firm value, while both firm size and capital structure do not demonstrate statistically meaningful effects on firm value. Capital structure successfully proves its mediating role in the relationship between firm size and firm value, yet it fails to do so for the relationship between profitability and firm value. This study is expected to make a meaningful contribution to financial literature, particularly in relation to capital structure decision-making within the food and beverage industry